Synthesis, Characterization and Anticancer Activity of some Metal Complexes of New Ligand Derived from 4-Methylbenzohydrazide with Computational Studies - Enass J. Waheed (Iraqi Journal of Pharmaceutical Sciences, 2025)
The aim of this research is to prepare a set of complexes with the general formula [M(HMB)n] , where M=VO (II) , Cr(III) and Cu(II) while n=2,3,2 respectively resulting from the reaction of anew ligand [N'-(2-hydroxy-3-methoxybenzyl)-4-methylbenzohydrazide] (HMB) derived from the reaction of the tow substances (4-methylbenzohydrazide and 2-hydroxy-3-methoxy benzaldehyde) with metal ions. The prepared compounds were identified by several spectroscopic methods such as Infrared, Nuclear Magnetic Resonance and Electronic Spectra. From the results of the measurements, it was suggested that the prepared complexes have different geometries such as square planar (Cu), square pyramidal (VO) and octahedral (Cr). DFT simulations backed up the experimental evidence. The geometries of ligand (HMB) and its complexes were thoroughly optimized using Gaussian 09w in DFT calculations, and numerous molecular characteristics were determined as well. The results showed that the metal complexes investigated are more stable than the free ligand (HMB). Molecular docking was used on E. coli and S. aureus proteins to estimate the probable binding energy of inhibitors. The activity of the compounds to inhibit different types of bacteria E. coli (negative) and S. ‎aureus (positive) was investigated.‎ where investigations revealed that the Cu-complex exhibited a stronger capacity to inhibit both types of bacteria than the ligand (HMB). The ligand and its copper complex were investigated for anticancer activity against HepG2 cells and normal cell WRL-68.